Study on extrahepatic manifestations in patients with hepatitis A in a tertiary care hospital - Asish Banerjee; Aneesh Debbarman; Sumaita Ahmed (Asian Journal of Medical Sciences, 2024)
Background: Hepatitis A is a common self-limiting infection of the liver. In recent times, there is a change in the pattern of hepatitis A infection producing extrahepatic manifestations. Aims and Objective: Our aim of the study is to find the profile of extrahepatic manifestations of hepatitis A. The secondary objective is to find a correlation of liver function test values with extrahepatic manifestations. Materials and Methods: A retrospective study was conducted over 3 years. 169 seropositive school-going cases were presented with signs and symptoms of hepatitis A and were clinically assessed. Results: Among 169 immunoglobulin M (+)ve hepatitis A, 36% of patients (61 cases) presented with extrahepatic features. Among the 61 patients, 41 patients presented with aspartate transaminase (AST):alanine transaminase (ALT) >2:1 and 20 patients presented with AST:ALT <2:1. Conclusion: In recent times, there has been a changing pattern in the presentation of hepatitis A producing extrahepatic manifestations in the pediatric age group.